Effects of dietary flavonoids intake in Saudi patients with coronary heart disease - Mohammed A Alsaif; Latifa A Khan; Adel A.H. Alhamdan; Saada Alorf; Abdulaziz M Al-Othman; Shatha Alawami (Wolters Kluwer Medknow Publications, 2007)
Objectives: The aim of the study was to assess the dietary intake of flavonoids and their effect on serum lipid levels in Saudi patients with coronary heart disease (CHD). Methodology: A cross-sectional study with a sample of 50 CHD patients and 50 controls. A 24-hour recall method was used to collect data on the dietary intake of macronutrients, flavonoids, and antioxidant vitamins. A food frequency questionnaire (FFQ) was used to collect data on habitual consumption during the year preceding the interview. Baseline data collection included medical history, anthropometric measurements, physical activity, and smoking status. Results: CHD patients showed significantly less intake of fruits and vegetables compared to the controls. Serum lipids including total cholesterol (TC), triglycerides (TG), and low density lipoproteins (LDL) were found to be significantly higher in CHD patients than in the controls. The main sources of flavonoids in a typical Saudi diet are tea, fruits (apples), vegetables (onions), and chocolate. The intake of flavonoids and antioxidant vitamins was significantly lower in CHD patients compared to the controls. A negative correlation between the dietary intake of different flavonoids and serum LDL was observed in CHD patients. Significant correlation was found between the intake of flavonol and waist to hip ratio Conclusions: The findings of the study support a potential protective effect of dietary flavonoids in relation to CHD. The study showed that consuming more Flavonoids may have positive effect on lowering blood lipids.